Analysis of Soil Erosion Hazardous Level In Jatipurno Sub-District Of Wonogiri District - Apriani Widiatiningsih; Mujiyo Mujiyo; Suntoro Suntoro (Graduate School Bogor Agricultural University (SPs IPB), 2018)
The aim of this research was to analyze erosion hazardous level (TBE) and predict the actual erosion (A) at Jatipurno Sub-District and planning of soil conservation when the actual erosion is more than the threshold at Jatipurno District. The USLE (Universal Soil Loss Equation) was used to predict actual erosion and erosion hazardous level then planning of soil conservation. The result showed that actual erosion level was varied from very light to heavy. The very light erosion, in range 0,2 ton/ha/yr to 7,8 ton/ha/yr the areas is about 1.879,19 ha (43,5%). The light erosion is 51,96 ton/ha/yr the areas is about 788,40 ha (18,3%). The moderate erosion is 92,83 ton/ha/yr the areas is about 694.95 ha (16,1%). The heavy erosion in range 209,84 ton/ha/yr to 377,21 ton/ha/yr the areas is about 952,80 ha (22,1%). Erosion hazardous level was varied from very light to very heavy. The very light erosion hazardous level covered areas of 1.034,77 ha (23,98%), the light erosion hazardous level covered areas 1.443 ha (33,44%), the heavy erosion hazardous level covered areas 1.204 ha (27,91%), the very heavy erosion hazardous level covered areas 632,88 ha (14,67%). Actual erosion dominated by very light level and TBE by the light level. Soil conservation planning is carried out by vegetative and mechanical conservation measures, such as planting variations of cover crops and terraces built in accordance with slope land and soil depths, land management according to local environmental and cultural preservation regulations and cooperation of all parties in environmental management can be done to prevent and minimize erosion.